Power-Integrated Circuit Active Leakage Current Detector. (29th May 2012) - Bulacio, M. F.; González, T. A.; Marinelli, G.; Alonso, R.; Tacca, H. E.
Abstract : Most of the failures of induction motors become insulation faults, causing a permanent damage. Using differential current transformers, a system capable of insulation fault detection was developed, based on the differential relay protection scheme. Both signal injection and fault detection circuitry were integrated in a single chip. The proposed scheme is faster than other existing protection and not restricted to protect induction motors, but several other devices (such as IGBTs) and systems. This paper explains the principle of operation of fault protection scheme and analyzes an integrated implementation through simulations and experimental results. A power-integrated circuit (PIC) implementation is presented.